2021
DOI: 10.1177/23247096211013206
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Therapy in the Management of Patients With Severe Rectal Bleeding Following Transrectal Ultrasound-Guided Prostate Biopsy: A Case-Based Systematic Review

Abstract: Rectal bleeding is a known complication of transrectal ultrasound-guided prostate biopsy. It is usually mild and resolves spontaneously. However, massive life-threatening hemorrhage can also rarely occur in this setting, potentially presenting a therapeutic conundrum. We hereby delineate the case of a patient who experienced severe intermittent lower gastrointestinal bleeding following a transrectal ultrasound-guided prostate biopsy. Traditional tamponade methods failed to control the hemorrhage. Subsequently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 54 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…ing after transrectal prostate biopsy [5]. In addition, this case highlights the importance of early endoscopic intervention to improve the patient's outcome in such cases.…”
Section: Endoscopy_uctn_code_ttt_1aq_2azmentioning
confidence: 79%
See 1 more Smart Citation
“…ing after transrectal prostate biopsy [5]. In addition, this case highlights the importance of early endoscopic intervention to improve the patient's outcome in such cases.…”
Section: Endoscopy_uctn_code_ttt_1aq_2azmentioning
confidence: 79%
“…The mucosal defect created by the biopsy needle might have caused the exposure of the underlying submucosal artery to the rectal lumen. A recent case-based systematic review reported the efficacy of endoscopic therapy for severe bleeding after transrectal prostate biopsy 5 . In addition, this case highlights the importance of early endoscopic intervention to improve the patient’s outcome in such cases.…”
Section: Figmentioning
confidence: 99%
“…Given post-TRUS-guided biopsy bleeding is rare and often managed by urologists, not much data have been reported to establish the superiority of monotherapy compared with combination endoscopic management. 5 …”
Section: Discussionmentioning
confidence: 99%
“…Given post-TRUS-guided biopsy bleeding is rare and often managed by urologists, not much data have been reported to establish the superiority of monotherapy compared with combination endoscopic management. 5 Several factors have been identified to increase the risk of post-TRUS-guided biopsy bleeding. Patients with a rich vascular bed surrounding the rectum and prostate, which are supplied from the inferior vesicular arteries, the middle and inferior rectal arteries, and dense submucosal venous plexus, could be at higher risk of bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…If proctoscopy is routinely performed when hemostasis is difficult, it may be helpful to predict the site of bleeding without proctoscopy. In addition to endoclipping, endoscopic therapeutic techniques include injection sclerotherapy, thermocoagulation, band ligation, and combination therapies 3 . Because urologists do not usually perform the above endoscopic therapies, assistance from a gastrointestinal endoscopist or colorectal surgeon should be required when endoscopic therapy is necessary.…”
mentioning
confidence: 99%